2015
DOI: 10.1002/mrc.4255
|View full text |Cite
|
Sign up to set email alerts
|

DOSY NMR and MALDI‐TOF evidence of covalent binding the DNA duplex by trimethylammonium salts of topotecan upon near UV irradiation

Abstract: Using DOSY NMR and MALDI-TOF MS techniques, we present evidence that quaternary trimethylammonium salts of topotecan, [TPT-NMe3 ](+) X(-) (X = CF3SO3, HCOO), bind covalently the natural DNA oligomer upon near UV irradiation in water under physiological conditions. It is shown that formate salt is very reactive at pH 7 and requires short irradiation time. This weak irradiation at 365 nm paves the way for a new application of TPT derivatives in clinical use, which can dramatically increase the therapeutic effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…be useful and have reported that the trimethylammonium salts of TPT alkylate DNA oligomers under near-UV irradiation. 16 Further attempts in this direction led us to the discovery of compounds that spontaneously bind to DNA oligomers and can therefore be used in vivo as Top I inhibitors in tumour chemotherapy. Scheme 2 shows the suggested course of a reaction in aqueous solution under near-biological conditions.…”
mentioning
confidence: 99%
“…be useful and have reported that the trimethylammonium salts of TPT alkylate DNA oligomers under near-UV irradiation. 16 Further attempts in this direction led us to the discovery of compounds that spontaneously bind to DNA oligomers and can therefore be used in vivo as Top I inhibitors in tumour chemotherapy. Scheme 2 shows the suggested course of a reaction in aqueous solution under near-biological conditions.…”
mentioning
confidence: 99%
“…Camptothecins selectively bind to the binary covalent complex DNA‐Top I, however this is a weak interaction. Previous study has shown that trimethylamonium salts of TPT can undergo photochemical transformation to intermediate product such as quinone methide (QM), which can alkylate DNA oligomers . Here, we present synthesis, physicochemical studies of 9‐aminomethyl substituted SN38 derivatives, evidence of their interactions, and spontaneous alkylation of the natural DNA octamer.…”
Section: Introductionmentioning
confidence: 91%
“… The part of the MALDI–MS spectrum of negative ions showing the mother peak for the neat parent nicked decamer, at m / z = 6885.8 ([M − H] − ), and a peak of the biohybrid of 2 with decamer 1 at m / z = 7290.9. The difference in masses M = 405 is due to transient intermediate o -methylene quinone formed from parent compound 2 or 3 [ 14 ]. …”
Section: Figures Schemes and Tablesmentioning
confidence: 99%
“…During the course of earlier research on camptothecin derivatives, we presented evidence for the formation of a molecular complex with the camptothecin core of topotecan (Hycamtin™), which occurred via selective interaction with the ultimate GC base pair in a natural DNA oligomer [ 12 ] and inside the nick of the model nicked DNA decamer [ 5 , 13 ]. Further studies [ 14 ] led us to disclose new SN38 derivatives that spontaneously alkylate DNA oligomers [ 15 , 16 , 17 ]. Covalent binding was confirmed in model 2′-deoxyguanosine (dG) [ 18 ], 2′-deoxycitidine (dC) [ 19 ], and 2′-deoxyadenosine (dA) [ 20 ] nucleosides.…”
Section: Introductionmentioning
confidence: 99%